Odoo's Enterprise Resource Planning Implementation Fostering Export Sales Business Agility in SMES Naruna Ceramic - Alma Shinta Dewi; Jumi - Jumi; Bayu Setyo Nugroho (Politeknik Negeri Semarang, 2023)
A dynamic business world is being created by the rapidly growing technology. This condition requires businessperson to be able to implement technology into their business processes. The implementation of an integrated information system can be done to increase the effectiveness of employee performance. An integrated information system called Enterprise Resource Planning can be implemented to increase the effectiveness of employee performance. Naruna Ceramic is a UMKM located at Jl. Sawosari No. 2 Bugel, Salatiga. Naruna Ceramic is an exporter that manages its export sales data manually, so there are no data integration between departments, resulting in a lack of effectiveness in employee performance. In this research, an information system design was carried out to boost business performance at Naruna Ceramic UKM by deploying Odoo ERP. The application method utilized is Rapid Application Development (RAD). The three steps of RAD are requirements planning, system design, and implementation. The User Acceptance Test (UAT) method is used to test the system. The test findings demonstrate how well the system meets business requirements, making its installation at UKM Naruna Ceramic very suited and successful in fostering business agility